Analisis Ketangguhan Impak dan Karakter Patahan Komposit Sandwich Serat Rami–Epoksi Berbasis Corrugate Cardboard - Zulkifli, Zulkifli; Dharmawan, Ida Bagus; Akbar , Syaeful; Zulfati Yusrina , Yasmin; Sanchia Samosir, Devina; Amin , Mohamad; Prayoga, Rafli (MACHINERY Jurnal Teknologi Terapan, 2025)
The combination of hemp fibers and epoxy resin in a sandwich structure offers a balance between stiffness and light weight, especially when using corrugated cardboard as the core material. However, the effect of fiber orientation on impact energy absorption and fracture characteristics in natural fiber-based sandwich composites has rarely been studied in depth. This study aims to analyze the effect of fiber orientation on the impact toughness and fracture morphology of hemp fiber–epoxy sandwich composites with corrugated cardboard cores. Hemp fiber is used as a natural reinforcement because it is lightweight, renewable, and has good mechanical strength. The composite panels were arranged in three fiber orientations —longitudinal (0°), transverse (90°), and plain weave —using the vacuum bagging method. Bisphenol-A epoxy resin served as the matrix, while the core came from double-wall cigarette carton waste. Impact testing was conducted using the Charpy method in a flatwise configuration in accordance with ISO 179-1:2023 to assess the panel's ability to absorb impact energy. The results show that fiber orientation significantly affects energy absorption and impact toughness. The 0° orientation produced the highest energy (2.854 J) and toughness of 30.43 kJ/m², while the 90° and plain weave orientations decreased by 36% and 70%, respectively. Macroscopic observations revealed characteristic failure patterns: 0° exhibited microcracks and core shear fractures; 90° showed fiber pull-out and delamination; while Plain weave displayed fiber bridging and brittle cracks. Longitudinal orientation provided the best impact toughness and the most efficient load transfer